Extracorporeal Detoxification in Abdominal Sepsis in Cancer Patients - N. D. Ushakova; O. I. Kit; A. A. Maslov; A. P. Men'shenina (Общая реаниматология)
The purpose is to evaluate the detoxification effects of the polymyxin sorption columns and filtration detoxification using polymethyl methacrylate membranes in abdominal sepsis in cancer patients.Materials and Methods. We examined 226 patients with oncological diseases of abdominal organs complicated by abdominal sepsis postsurgery. In 50 cases, septic shock was reported. In 173 patients an acute renal injury (ARI) was diagnosed in the structure of organ failures, of which a combination with acute respiratory distress syndrome (ARDS) was diagnosed in 61 patients. The severity was 26.3±3.3 points (APACHE-II scale), 10.2±2.5 points (SOFA scale), and 4.3±1.8 points (qSOFA scale). Microbiological identification was obtained in 155 (68.6%) cases. The polymyxin column sorption was used in 86 patients 2–6 hours after sepsis was diagnosed with the EAA greater than 0.5. The blood flow rate was 80–150 mL/min; the duration was 120–240 min; the sorption frequency was 2–3 sessions at a 24-hour interval. If ARI and ARDS were developed, detoxification by filtration using a dialyzer with a BK-1.6F polymethylmethacrylate membrane was included in the complex treatment of 144 patients. The detoxification was carried out for 8–12 hours changing the dialyzer every 4 hours.Results. A statistically significant decreases of hyperthermia, leukocytosis, neutrophilia, procalcitonin, and the EAA test values were revealed after the completion of the sorption treatment. Normalization of hemodynamic parameters, increase of the oxygenation index, and SOFA scoring decrease by 5.6±2.1 points (P<0.05) were found. PCT and IL-6 blood levels decreased from 6.7±2.7 ng/mL to 2.3±0.6 ng/mL and from 7300±7700 pg/mL to 860±180 pg/mL, respectively, as determined 60 minutes after completion of filtration detoxification procedure (P<0.05). The SOFA index decreased by 4.1±1.1 points (P<0.05).Conclusion. The use of polymyxin column sorption and filtration detoxification using a polymethyl metacrylate membrane improves the results of treatment of abdominal sepsis in cancer patients.